2022
DOI: 10.1021/acssuschemeng.2c03313
|View full text |Cite
|
Sign up to set email alerts
|

Lambda Carrageenan as a Water-Soluble Binder for Silicon Anodes in Lithium-Ion Batteries

Abstract: The large volume expansion of a silicon (Si) anode causes severe mechanical failure, limiting its use in lithium-ion batteries (LIBs). Using functional polymers as a binder material is an approach to this issue. We explore the applicability of the water-soluble natural polysaccharide lambda carrageenan (CGN) as a binder for Si nanoparticles in LIBs. The characteristic binder properties of commercial (CGN-com) and custom (ext-CGN) CGNs are investigated. CGN binders exhibit excellent mechanical characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 66 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…They are also highly resistant to autoignition, involve relatively low processing costs, and can form hydrogen bonds with the Si within the anode, a process that leads to improvements in the adhesive, mechanical, and electrochemical properties . Poly­(acrylic acid) (PAA), , poly­(acrylamide) (PAM), , poly­(vinyl alcohol) (PVA), , and polysaccharide-type materials, including carboxymethyl cellulose (CMC), , sodium alginate (SA), , and carrageenan (CGN), , are a few of the most popular aqueous polymer binders. These binders have improved cycle stability for LIBs compared to poly­(vinylidene fluoride), or PVDF, which is widely used as both a cathode and anode binder for LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…They are also highly resistant to autoignition, involve relatively low processing costs, and can form hydrogen bonds with the Si within the anode, a process that leads to improvements in the adhesive, mechanical, and electrochemical properties . Poly­(acrylic acid) (PAA), , poly­(acrylamide) (PAM), , poly­(vinyl alcohol) (PVA), , and polysaccharide-type materials, including carboxymethyl cellulose (CMC), , sodium alginate (SA), , and carrageenan (CGN), , are a few of the most popular aqueous polymer binders. These binders have improved cycle stability for LIBs compared to poly­(vinylidene fluoride), or PVDF, which is widely used as both a cathode and anode binder for LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing focus on carbon neutrality and green growth, significant momentum has been gained in the shift from internal combustion engine vehicles to electric vehicles. Driven by the rapidly growing trend of electric vehicles, there is a substantial demand for lithium-ion batteries (LiBs) that exhibit high energy density, safety, and cycling stability. Silicon (Si) is a promising anode material for LiBs due to its high theoretical capacity of approximately 4200 mAh g –1 and relatively low discharge voltage of <0.5 V vs Li/Li + . However, the delithiation/lithiation process may lead to the formation of the alloy phase (Li 4.4 Si), resulting in an approximate 300% volume fluctuation, which may trigger the detachment of Si nanoparticles from the Cu foil and interrupt electronic transportation during extended cycling. , Consequently, Si-based electrodes still suffer from a significant deterioration in capacity and reduced cycle life. …”
Section: Introductionmentioning
confidence: 99%
“…The use of electrolyte additives, such as FEC and vinylene carbonate, is required to improve the cycling performance; , in particular, FEC is predominantly used in studies on silicon electrodes. FEC reductively decomposes on the electrode surface to form a fluorine-rich SEI, such as LiF, which can effectively passivate the electrode surface, leading to enhanced long-term cyclability. , Furthermore, we have reported that FEC is effective in lithium batteries as well as in improving the cycling performance of Na x P electrodes in Na-ion batteries, NaNi 1/2 Mn 1/2 O 2 //hard carbon full cells, and in the plating-stripping reaction of Na metal. , Therefore, it is important to investigate the effect of FEC on silicon electrodes to improve their cycling performance.…”
Section: Introductionmentioning
confidence: 99%